Evaluation of Sericin/Polyvinyl Alcohol Mixtures for Developing Porous and Stable Structures - Maria C. Arango; Leander Vásquez Vásquez; Akemy Carolina Homma Parra; Santiago Rueda-Mira; Natalia Jaramillo-Quiceno; Josep Pasqual Cerisuelo; Amparo Cháfer; Catalina Álvarez-López (Biomimetics)
Fibrous by-products, including defective or double cocoons, are obtained during silk processing. These cocoons primarily contain fibroin and sericin (SS) proteins along with minor amounts of wax and mineral salts. In conventional textile processes, SS is removed in the production of smooth, lustrous silk threads, and is typically discarded. However, SS has garnered attention for its antioxidant, antibacterial, biocompatible, and anticancer properties as well as its excellent moisture absorption, making it a promising polymer for biomedical applications. Owing to its functional groups (carboxyl, amino, and hydroxyl), SS can blend and crosslink with other polymers, thereby improving the mechanical properties of sericin-based materials. This study explored the effects of different SS/polyvinyl alcohol (PVA) ratios on porous scaffolds fabricated via freeze-drying, focusing on the mechanical stability, water absorption, and protein release in phosphate-buffered saline (PBS). The scaffold morphology revealed reduced porosity with higher SS content, while increased PVA content led to material folding and layering. A greater PVA content enhanced water absorption, mechanical properties, and thermal stability, although SS release decreased. These results demonstrate that scaffold properties can be tailored by optimizing the SS/PVA ratio to suit specific biomedical applications.